Influence of High Temperature Thermal Radiation on the Transition Characteristics of Coal Oxidation and Spontaneous Combustion - Wang, Liancong; Hu, Weizhao; Hu, Yuan (Frontiers in Materials, 2021)
In the goaf of the coal mine, there will be some high-temperature points before or during the fire. Under certain conditions, these high-temperature points will radiate heat to the surrounding coal in the form of thermal radiation, which, in turn, may also ignite the coal. Taking this situation into consideration, this study aims to investigate the influence of high-temperature thermal radiation on the transformation characteristics of coal oxidation and spontaneous combustion using the high-temperature thermal radiation method. The results show that an increase in thermal radiation value reduces the ignition time of coal gradually. The peak heat release rate, total heat release, peak smoke release rate, and total smoke release gradually increase. Additionally, the total carbon monoxide release reduces gradually, and the peak carbon dioxide production rate increases gradually. It is worth noting that as the heat radiation value increases, the peak value of CO production rate of lignite and bituminous coal is noted to decrease gradually, whereas that of anthracite increases gradually. The total carbon dioxide emissions of bituminous coal and anthracite increased gradually, whereas the total carbon dioxide emissions of lignite increased first and then decreased.